Makna Syukur dalam Musik Video Yura Yunita di Youtube - Ranti Fazrin; Alex Sobur (UNISBA Press, 2023)
Abstract. The research entitled The Meaning of Gratitude in Yura Yunita's Music Video on Youtube is motivated by how the signs presented as gratitude through music videos are currently in demand by a wide audience. Music videos are a medium for musicians to convey meaningful messages to their listeners. This study aims to determine the meaning of gratitude in the music video “Dunia Tipu-Tipu” through John Fiske's semiotic theory and approach. The research method used is qualitative. Observation and Documentation as data collection techniques in this study as well as data analysis techniques in terms of the level of reality, the level of representation and the level of ideology. The results of the study show that the meaning of gratitude in the music video